Retrograde Signals Navigate the Path to Chloroplast Development . Issue 2 (18th December 2017) - Hernández-Verdeja, Tamara; Strand, Åsa
Abstract : Complex signaling networks between the chloroplast and the nucleus mediate the emergence of the seedling into the light and the establishment of photosynthesis.